Pengaruh Inflasi dan Suku Bunga dan Nilai Tukar Rupiah serta Jumlah Uang Beredar terhadap Return Saham - Hidayat, La Rahmad; Setyadi, Djoko; Azis, Musdalifah (FORUM EKONOMI, 2017)
This research is to examine the effect of inflation, interest rate, exchange rate and money supply on stock returns LQ 45 listed on the Indonesia Stock Exchange. The object of this research is the return - shares out of the category LQ 45 years of research by 2010-2015. Its Sampling using purposive sampling and get the 24 stocks that meet the criteria of 45 stocks LQ 45 as a sample. Thus, the number of samples studied was 144 shares for 6 years. The method used is multiple linear regression analyzes that examine whether or not a significant variable - the independent variable on the dependent variable. Based on the results known that R indicates that there is an ideal relationship of Inflation, Interest Rate, Exchange Rate and Money Supply toward to Return shares in LQ 45. R square indicates that the variable inflation rates, interest rates, the value of exchange rate and the money supply can explain the variable return shares at LQ 45 index. Based on F test indicates the same that the variable inflation rate, interest rate, exchange rate and money supply have a significant influence on shares returns in LQ 45 listed on Indonesia Stock Exchange. The results of T test showed that the rate of inflation significant and negative effect on shares returns and interest rates positive and significant effect on shares returns while exchange Rate and the money supply no significant effect on shares returns in LQ 45 Listed on Indonesia Stock Exchange.Keywords: stock return, Inflation, Interest Rate, Exchange Rate, Money Supply.